RESEÑA de: Vázquez González, S.; Cid de León Bujanos, B. G. y Montemayor Rodríguez, E. (coords.) Riesgos y Trabajo Social / Risks and Social Work. Universidad Autónoma de Tamaulipas, México 2016 - González Aguado, Ruth (Comunitania. Revista Internacional de Trabajo Social y Ciencias Sociales, 2017)
-